SARS-CoV-2-Specific T Cell Responses Are Not Associated with Protection against Reinfection in Hemodialysis Patients. Issue 5 (May 2022) - Shankar, Sushma; Beckett, Joseph; Tipton, Tom; Ogbe, Ane; Kasanyinga, Mwila; Dold, Christina; Lumley, Sheila; Dengu, Fungai; Rompianesi, Gianluca; Elgilani, Faysal; Longet, Stephanie; Deeks, Alexandra; et al.
Significance Statement: Patients on hemodialysis (HD) are vulnerable to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and mount poor neutralizing antibody responses after two-dose vaccination. Although serological responses have been associated with reduced rates of reinfection, the relationship between cellular immunogenicity and protection has not been established. We report, for the first time, high incidence of reinfection in patients on HD who are vaccine naive (25%), which identifies that T cell responses do not predict protection against reinfection. Instead, patients on HD who went on to become reinfected had mounted highly variable and sometimes robust proliferative T cell responses to a broad array of SARS-CoV-2 peptide pools during the primary infection. The understanding that SARS-CoV-2–specific T cell responses are not predictive of protection against future infection will be a critical issue when measuring clinical efficacy of vaccination in these vulnerable cohorts, particularly when facing rapidly emerging variants of concern.